Meinongian extensions of predicates - Sierszulska, Anna (Logic and Logical Philosophy, 2005)
The paper analyses the contemporary notion of an extension of a predicate from the perspective of semantics typical for Meinongian logics, and in opposition to the traditional notion of extension. This leads to a discussion of the types of properties that can be predicated about objects as belonging to the sets of properties ascribed to them, and such that can be predicated about them only ‘externally’. It is also problematic in which sense nonexistent objects possess the properties ascribed to them. The concluding remarks concern some issues related to the truth of predications about nonexistent objects, which is the basic condition to admit them as belonging to the extensions of predicates in the first place.